Diplomacy at the United Nations - Kent, William (My University, 1966)
This thesis examines one of the most useful instruments yet devised for regulating the relations of states diplomacy. It explains how, from the beginning of the modern state system, traditional diplomacy has served the needs of the international community.
The major part of this study focuses on the diplomatic activities that take place at the United Nations, especially as they concern the Security Council, the General Assembly, and the Secretariat with the Secretary General. Support is presented for the contention that traditional, "quiet" diplomacy plays an important role at the United Nations, even though on the surface the United Nations appears to be pre-occupied with public debate, vote swapping, and distortion of basic international issues.
The role of small nations in an international society is also briefly discussed.
Keywords: Diplomacy; United Nations; diplomatic activities; Security Council